Anticholinesterases and antioxidant alkamides from Piper nigrum fruits. Issue 17 (1st September 2016) - Tu, Yanbei; Zhong, Yujiao; Du, Hongjian; Luo, Wei; Wen, Yaya; Li, Qin; Zhu, Chao; Li, Yanfang
Abstract: The anticholinesterase and antioxidant effects of five different extracts of Piper nigrum were evaluated. Twenty-one known alkamides were isolated from active ethyl acetate extract and investigated for their cholinesterase inhibitory and antioxidant effects. Among them, piperine (2 ), piperettine (5 ) and piperettyline (20 ) exhibited dual inhibition against AChE and BChE, and feruperine (18 ) was the most potent selective inhibitor of BChE. Molecular docking simulation was performed to get insight into the binding interactions of the ligands and enzymes. In addition, N -trans-feruloyltyramine (3 ) contributed to the strongest DPPH radical-scavenging activity. The self-induced A β aggregation inhibition of2, 5 and18 was further evaluated. Results indicated that some alkamides could be multifunctional lead candidates for Alzheimer's disease therapy. Graphical abstract: